2021
DOI: 10.3389/fonc.2020.614487
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishable Prognostic miRNA Signatures of Head and Neck Squamous Cell Cancer With or Without HPV Infection

Abstract: Since their discovery in the 1990’s, microRNAs (miRNA) have opened up new vistas in the field of cancer biology and are found to have fundamental roles in tumorigenesis and progression. As head and neck squamous cell carcinoma (HNSCC) with positive human papillomavirus (HPV+) is significantly distinct from its HPV negative (HPV−) counterpart in terms of both molecular mechanisms and clinical prognosis, the current study aimed to separately develop miRNA signatures for HPV+ and HPV− HNSCC as well as to explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…Not only the methylation of other genes and other genomic regions, but also other players, including noncoding RNAs and chromatin remodelers, should be explored. For example, global hypomethylation, associated with poor prognosis in other cancer types [189,[309][310][311], seems to differ according to HPV status and could help explain the prognosis differences observed. Furthermore, mutations in the histone methyltransferases NSD1 and NSD2 define a group of good prognosis among LSCC patients, but not in other HNSCC subtypes [312]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only the methylation of other genes and other genomic regions, but also other players, including noncoding RNAs and chromatin remodelers, should be explored. For example, global hypomethylation, associated with poor prognosis in other cancer types [189,[309][310][311], seems to differ according to HPV status and could help explain the prognosis differences observed. Furthermore, mutations in the histone methyltransferases NSD1 and NSD2 define a group of good prognosis among LSCC patients, but not in other HNSCC subtypes [312]…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, miRNA signatures according to HPV status were reported in HNSCC. By comparing HPV-positive and HPV-negative tumors with adjacent tissue, 282 and 289 differentially expressed miR-NAs were identified, respectively [189]. Although these numbers were similar, when specific survival-associated miRNAs were evaluated, the expression of 39 miRNAs was associated with prognosis among HPV-positive patients, 16 among HPV-negative patients, and no miRNA was shared.…”
Section: Hnscc Etiology and Epigenetics: Hpvmentioning
confidence: 96%
“…Analyzing data obtained from 515 HNSCC samples and 44 normal tissues, Luo et al highlights deregulated miRNAs for both positive and negative HPV HNSCC cases [ 96 ]. In the patient lot including 97 HPV + patients, 282 miRNAs were identified and after statistical analysis, a 7 miRNA signature was considered proper for its prognostic value.…”
Section: Mirna In Head and Neck Cancers—from The Biomarker Of The Fut...mentioning
confidence: 99%
“…Cases of HPV− with a high risk of miRNAs could benefit more from target therapies and HPV+ patients with a low risk of miRNAs could benefit more from immunotherapy. The authors mention metabolic disorder as a possible cause of therapeutic failure in HPV− patients with an increased miRNA risk score [ 66 , 67 , 96 ].…”
Section: Mirna In Head and Neck Cancers—from The Biomarker Of The Fut...mentioning
confidence: 99%
“…They showed that immune-related pathways in HPV + tumours were mainly associated with low-risk scores. HPV − tumours, with characteristic high-risk scores, showed instead upregulation of metabolic and other vital oncogenic pathways [ 28 ]. It has further been shown that targeting the HPV16/18 viral oncogenes or neoantigens E6 and E7 by immunotherapy in HPV + tumours generated durable immune responses in the tumours, adding these proteins to the list of most promising targets in HNSCC.…”
Section: Introductionmentioning
confidence: 99%